1999
DOI: 10.1108/09604529910248821
|View full text |Cite
|
Sign up to set email alerts
|

Assessing service management effectiveness in a health resort: implications of technical and functional quality

Abstract: This study assessed the technical (tangible) and functional (human interaction) quality of services in a first-class international health resort and related these to service management effectiveness. Service management is effective when customers judge the overall service quality to be good, they are highly satisfied, they are willing to recommend the firm to others and they intend to repurchase or are predisposed to purchase additional services from the firm. The technical and functional aspects of services q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 14 publications
1
39
0
2
Order By: Relevance
“…We suggest that separating the service offering into core and peripheral attributes of the service enables a more rigorous assessment of the elements critical to RI. Separation of the service aspects is supported by Ferguson et al (1999) who found that technical and functional aspects of services quality and their relation to service management effectiveness, were different between the core and supplementary services. This supports the need for a more thorough analysis of core and supplementary service elements and their relationships to value, satisfaction and RI.…”
Section: Defining the Constructs Core And Supplementary Servicementioning
confidence: 91%
See 1 more Smart Citation
“…We suggest that separating the service offering into core and peripheral attributes of the service enables a more rigorous assessment of the elements critical to RI. Separation of the service aspects is supported by Ferguson et al (1999) who found that technical and functional aspects of services quality and their relation to service management effectiveness, were different between the core and supplementary services. This supports the need for a more thorough analysis of core and supplementary service elements and their relationships to value, satisfaction and RI.…”
Section: Defining the Constructs Core And Supplementary Servicementioning
confidence: 91%
“…The core service is the basic reason for the business to be in the market and represents the firm's basic competency in creating value in the first instance (Ferguson, Paulin, Pigeassou, & Gauduchon 1999). For the performing arts sector this would be the display and performance of acts or skills in a public performance.…”
Section: Defining the Constructs Core And Supplementary Servicementioning
confidence: 99%
“…Respondent 2 (M, H) explained that, 'the role of service quality standards is to protect the interests of customers and to guarantee a minimum level of excellence'. To measure the quality of hot springs experience, previous studies have identified two key dimensions namely: functional quality (how the service was delivered) and technical quality (what was delivered) (Ferguson et al, 1999;Mueller and Kaufmann, 2001;Snoj and Mumel, 2002). A majority of respondents emphasised the functional aspects of the service rather than the technical aspects.…”
Section: Capabilities Of Destination Management Organizations Nearlymentioning
confidence: 99%
“…In this regard, the work by Joy and Sherry (2003) examining different determinants of art appreciation in a museum through qualitative research supports our research. Moreover, previous research in this context has found that the core and peripheral services have different impacts on service management effectiveness (Ferguson et al, 1999). Customers make their repurchase decisions based on the perceived quality of both core and peripheral services, mediated by perceived value and customer satisfaction (Hume, 2008 b).…”
Section: Introductionmentioning
confidence: 99%